Sensory Response of Durian Lai Tempoyak and Its Potential as A Functional Food - Marwati; Selviana Ave Maria Funan; Maulida Rachmawati; Aswita Emmawati; Miftakhur Rohmah; Agustu Sholeh Pujokaroni; Yudha Agus Prayitno; hamka nurkaya (Jurnal Loupe, 2024)
Tempoyak, a fermented food made from durian, is a popular seasoning in Malay communities in Malaysia and Indonesia. Produced using low-quality durian, it serves as an alternative to prevent spoilage. Tempoyak has functional benefits as it contains lactic acid bacteria (LAB), a probiotic providing digestive health benefits. Research on East Kalimantan's durian lai explores its potential for tempoyak production. The study, utilizing a Completely Randomized Design, examined salt concentrations and fermentation times. Optimal quality was achieved with a 5% salt concentration and a 7-day fermentation period, yielding favorable organoleptic results, with "liked" ratings for color and texture, and "somewhat liked" for aroma and taste. The hedonic quality included an orange-yellow color, sour aroma, salty taste, and soft texture. The total LAB reached 4.1 x 108 CFU/g, meeting probiotic criteria, with a pH of 3.85.